Rheological properties of porcine organs: measurements and fractional viscoelastic model - Mishra, A; Cleveland, R (University of Oxford, 2022)
This is research data that supports an article entitled "Rheological properties of porcine organs: measurements and fractional viscoelastic model" that has been submitted for publication. The file contains the experimental data measured stress and strain in shear and compression for various porcine tissues. It also has the fitting parameters determined for the mathematical models (semi fractional Kelvin-Voight) that were fit to the experimental data. The data is in an Excel spreadsheet.